Predictors of poor glycaemic control in older patients with type 2 diabetes mellitus - Shariff Ghazali, Sazlina; Ismail, Mastura; Cheong, Ai Theng; Bujang, Mohamad Adam; Haniff, Jamaiyah; Lee, Ping Yein; Syed Abdul Rahman, Syed Alwi; Chew, Boon How (Singapore Medical Association, 2015)
Introduction:We assessed the predictors of poor glycaemic control among older patients with type 2 diabetes mellitus (T2DM) in Malaysia.